Determination of the fluoride content of Malaysian commercial teas - Ardini, Yunita Dewi; Asri, Zuhair Muhammad; Azhar, Muhammad Mujahid; Lestari, Widya; Kusumawardani, Anisa; Haris @ Harith, Muhammad Salahuddin (Wolters Kluwer - Medknow, 2021)
Background: Tea ranks first as the most-enjoyed beverage worldwide. Nevertheless, tea is rich in fluoride due to its uptake and storage from the soil by tea plants. Moreover, limited information is available regarding the fluoride content of Malaysian teas. Objective: This study aims to quantify the amount of fluoride present in teas available in the Malaysian market. Methods: An exploratory research was conducted on commercially available infusion teas from Peninsular Malaysia between November 2016 and December 2017. The fluoride content of 106 tea samples from three groups, viz., black, green, and other tea types, respectively, was measured using ultraviolet–visible spectrophotometry. The results were analyzed by one-way analysis of variance and independent t-test. Results: All of the tea leaf samples contained fluoride content between 0.01 and 1.08 mg/L. Black, green, and red tea exhibited significantly different contents of fluoride (P = 0.028). Conclusion: Significant amounts of fluoride were present in teas found in Malaysian markets. Our study provides Malaysian consumers key information regarding the amount of fluoride present in their teas.